Effect of Pelargonidin isolated from Ficus benghalensis L. on phenotypic changes in zebrafish (Danio rerio) embryos - Uday Kundap; Yogini Jaiswal; Rachana Sarawade; Leonard Williams; Mohd. Farooq Shaikh (Elsevier, 2017)
In the present study, the extraction and isolation of Pelargonidin, an anthocyanin compound from stem bark of Ficus benghalensis are described. The study also involves evaluation of the effect of Pelargonidin on phenotypic variations in zebra fish embryos. Extraction and isolation of Pelargonidin were carried out by employing liquid-liquid extraction technique, phytochemical tests, column chromatography, UV and FT-IR. In the zebra fish embryo model, Paclitaxel was employed as a negative control. A series of phenotypic changes in different stages of embryonic development were studied with treatment concentrations of Pelargonidin between 3.0 and 20 ppm at 0-72-hour post-fertilization (hpf). The results of our studies indicate that, after exposure of zebra fish embryos to 3.3-20 ppm concentration of Pelargonidin for 72 h, a significant reduction in aortic development occurs. At the dose level of 0.5 ppm Paclitaxel and Pelargonidin in the dose range between 3.3 and 20 ppm, the zebra fish embryos were found to have bent tail, malformed eyes and developmental delays in vasculature. Based on the results obtained, we infer that Pelargonidin can exhibit phenotypic anti-angiogenic variations in embryonic stage of fish embryos and it can be applied in future for exploration of its anti-angiogenic potential. Furthermore, Pelargonidin could serve as a candidate drug for in vivo inhibition of angiogenesis and can be applied for the treatment of neovascular diseases and tumor.